تبني المسؤولية الاجتماعية كأحد متطلبات الصيرفة الإسلامية: تجربة مجموعة البركة المصرفية - العمري، أصيلة Alamri, Asilah; مهاوات، لعبیدي Mehaouat, Labidi (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2017)
This study aims to identify the importance and inevitability of Islamic banks' adoption of the principles and dimensions of social responsibility through their commitment to participate in some social activities, programs and ideas to meet the social requirements of the related parties and not only to achieve financial returns. In order to achieve this objective, Social responsibility and established its own committee of the Board of Directors. The study concluded that the financing of the loan is considered the most important requirement for the adoption of social responsibility in Islamic banks, in addition to sponsoring and supporting educational and social projects and improving the living conditions of the society. Al Baraka Banking Group regards social responsibility as an integral part of the Group's philosophy and vision, And this has been demonstrated by the compatibility of the principles of social responsibility with the provisions of Islamic law and Islamic ethics that the group operates according to its principles.
تهدف هذه الدراسة إلى التعرف على أهمية وحتمية تبني المصارف الإسلامية لمبادئ وأبعاد المسؤولية الاجتماعية من خلال التزامها بالمشاركة في بعض الأنشطة والبرامج والأفكار الاجتماعية لتلبية المتطلبات الاجتماعية للأطراف المترابطة به وعدم الاكتفاء بتحقيق العوائد المالية، ومن أجل تحقيق هذه الهدف تم اختيار مجموعة البركة المصرفية التي تبنت برنامجا خاصا للمسؤولية الاجتماعية وأقامت لجنة خاصة بها تابعة لمجلس إدارتها. وقد خلصت هذه الدراسة إلى العديد من النتائج أهمها: التمويل بالقرض الحسن يعتبر أهم متطلبات تبني المسؤولية الاجتماعية في المصارف الإسلامية بالإضافة إلى رعاية ودعم المشاريع التعليمية والاجتماعية، وتحسين الظروف المعيشية للمجتمع، كما أن مجموعة البركة المصرفية تعتبر المسؤولية الاجتماعية جزءا لا يتجزأ من فلسفة المجموعة ورؤيتها، وقد ظهر ذلك من خلال توافق مبادئ المسؤولية الاجتماعية مع أحكام الشريعة الإسلامية والأخلاق الإسلامية التي تعمل المجموعة وفقا لمبادئها.
Keywords: الاقتصاد الإسلامي -- البنوك الإسلامية -- المسؤولية الاجتماعية -- الصيرفة الإسلامية -- القرض الحسن -- الجزائر